Macroprudential and Monetary Policy: Loan-Level Evidence from Reserve Requirements - Cecilia Dassatti Camors; José-Luis Peydró; Francesc R.-Tous; Sergio Vicente (Universitat Pompeu Fabra (upf), Department of Economics and Business, 2019)
We analyze the impact of reserve requirements on the supply of credit to the real sector. For identification, we exploit a tightening of reserve requirements in Uruguay during a global capital inflows boom, where the change affected more foreign liabilities, in conjunction with its credit register that follows all bank loans granted to non-financial firms. Following a difference-in-differences approach, we compare lending to the same firm before and after the policy change among banks differently affected by the policy. The results show that the tightening of the reserve requirements for banks lead to a reduction of the supply of credit to firms. Importantly, the stronger quantitative results are for the tightening of reserve requirements to bank liabilities stemming from non-residents. Moreover, more affected banks increase their exposure into riskier firms, and larger banks mitigate the tightening effects. Finally, the firm-level analysis reveals that the cut in credit supply in the loan-level analysis is binding for firms. The results have implications for global monetary and financial stability policies
Keywords: E51; E52; F38; G21; G28; 330; macroprudential policy; reserve requirements